AN APPROACH TO HEALTH SERVICES DEVELOPMENT RESEARCH - F.Amini; Z.Jaksic; A.Khosrowshahi (Tehran University of Medical Sciences, 1973)
The process of planning and initiating health services development has been described as conceived and experienced by the working group of the Health Services Development Research Project in Iran. The technical steps (conceiving and describing the health services system, development of plans, preparatory step and implementation) as well as political support needed are defined and described. The importance of clear definition of the system is stressed as the basis for situational analysis and plans. Data are presented to illustrate findings during field observations in the province of West Azarbaijan. As a mechanism to initiate the proposed changes, the choice of direction of development and objectives, as well as to focus on critical and productive elements of the existing system specifically building of a new front-line of primary health care services , have been proposed. The "functional unity" of agencies and organizations participating in health delivery system and management tools for perpetuating of development, complete the plans. After discussion of alternative plans for development it is concluded that at present it is essential to look at service systems comprehensively, use the existing services as the point of departure aim at adequate coverage and provide service as required by the population and not as conceived by professional pressure groups.